Ethnic and Religious Diversity in Sarawak: Peacebuilding among Muslim Youth - Sharifah Nooraida (Al-Albab, 2017)
The ethnic and religious diversity in Sarawak is unique among Malaysians. The need for tolerance and unity regardless of the existence of various ethnics and religions is the key to building peace in Sarawak. The state of unity in Sarawak is sustained with the role of Islam as the official religion, the constitutional monarchy, community structure, political will, social awareness, positive peace, economic stability and education for gender equality. Muslim youth in Sarawak are also playing roles in promoting peace through esteemed programmes in an effort to engage peacebuilding among youths. 'Islam is the way of life' continues to be the principle in engaging Muslim youth towards peace. The Institute of Teacher Education (ITE) Batu Lintang Campus in Kuching, Sarawak is one of the higher learning institutions in Malaysia that is engaging youth in promoting peace. ITE Batu Lintang Campus participated in colouring Malaysia with ‘The Youth Peace Campaign’ accompanied by 394 youth from all over Sarawak. This paper aims to share the roles and opinions of the Muslim youth towards peace in their diversified ethnic and religious community. Although ITE Batu Lintang Campus endorsed no specific course accentuating on peacebuilding education, the youth in the campus are still the main asset for promoting peace in ethnic and religious diversity.